Brown rice: a missing nutrient-rich health food - Xiuxiu Wu; Tianyi Guo; Feijun Luo; Qinlu Lin (Food Science and Human Wellness)
Brown rice (BR) is a traditional health food being rich in various active substances, which have effective preventive and therapeutic effects on many diseases. In this review, we systemically summarized the efficacy of BR on cardiovascular diseases (CVDs), hyperlipidemia, hypertension, diabetes, obesity, osteoporosis, neurodegenerative diseases, cancer, immune disorders, inflammation, anxiety, liver and stomach damage, etc. Underlying mechanisms have also been analyzed, which include regulating lipid synthesis and metabolism, improving insulin levels and increasing glucose metabolism, anti-oxidation, promoting the immune system, transcription and non-transcriptional regulation, blocking cell cycle, thereby improving disease symptoms and reducing its recurrence rate. Generally, BR has been almost disappeared in modern society, but it is promising to exploit the potential to become a functional food. Further research on the nutritional value, variety differences, storage problems, taste and molecular mechanism of BR will be conducive to help meticulously design clinical intervention trials and ultimately improve the treatment and prevention of various diseases.